Stroke rehabilitation using noninvasive cortical stimulation: hemispatial neglect. (August 2012) - Mylius, Veit; Ayache, Samar S; Zouari, Hela G; Aoun-Sebaïti, Mehdi; Farhat, Wassim H; Lefaucheur, Jean-Pascal
The rehabilitation of neuropsychological sequels of cerebral stroke such as hemispatial neglect by noninvasive cortical stimulation (NICS) attracts increasing attention from the scientific community. The NICS techniques include primarily repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS). They are based on the concept of either reactivating a hypoactive cortical region affected by the stroke (the right hemisphere in case of neglect) or reducing cortical hyperactivity of the corresponding cortical region in the contralateral hemisphere (the left hemisphere). In the studies published to date on the topic of neglect rehabilitation, rTMS was used to inhibit the left parietal cortex and tDCS to either activate the right or inhibit the left parietal cortex. Sham-controlled NICS studies assessed short-term effects, whereas long-term effects were only assessed in noncontrolled rTMS studies. Further controlled studies of large series of patients are necessary to determine the best parameters of stimulation (including the optimal cortical target location) according to each subtype of neglect presentation and to the time course of stroke recovery. To date, even if there are serious therapeutic perspectives based on imaging data and experimental studies, the evidence is not compelling enough to recommend any particular NICS protocol to treat this disabling condition in clinical practice.